Uterine inversion during caesarean section: a case report - Raj, Anjaly; Roy, Kallol Kumar; Zangmo, Rinchen; Yadav, Anshu; Noor, Nilofar; Saha, Sushmita; Bairwa, Sonam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
The present report aim to sensitise the obstetrician regarding risk of uterine inversion in a scarred uterus and the importance of immediate manual replacement. Represented case is of 40 years gravida five with previous one spontaneous abortion and previous history of three ectopic pregnancies with history of open left salpingectomy for ruptured left tubal ectopic pregnancy and history of laparoscopic right tubal clipping and uterine rupture repair for cornual pregnancy underwent an emergency caesarean section at 34 weeks. Since there were no signs of placental separation, controlled cord traction of placenta was attempted and uterine inversion was noticed. Manual replacement of uterus was done followed by manual removal of the adherent placenta. There was no postpartum haemorrhage. Inversion of uterus during caesarean section is a rare obstetric complication. If unrecognized it could lead to serious morbidity due to haemorrhage and shock. Prompt diagnosis and repositioning of the uterus are important measures in management.